1995
DOI: 10.1113/jphysiol.1995.sp021073
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic control of rat supraoptic neurones during osmotic stimulation of the organum vasculosum lamina terminalis in vitro.

Abstract: 1. The effects of osmotic or electrical stimulation of the organum vasculosum lamina terminalis (OVLT) were examined during intracellular recordings (32°C) obtained from ninety-five supraoptic nucleus magnocellular neurosecretory cells (MNCs) in superfused explants of rat hypothalamus. 2. Brief (10-20 s) applications of hypertonic and hypotonic solutions to the area of the OVLT caused prolonged (> 1 min) increases and decreases, respectively, in electrical activity in seventy of seventy-four trials performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
147
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 33 publications
7
147
1
2
Order By: Relevance
“…This will prevent the postsynaptic neuron from being contaminated by nonrelevant signals and will serve to increase the signal-to-noise ratio for pertinent information (8). In the SON, glutamate spillover is likely to occur during the brief (2-to 4-s) high-frequency (40-to 80-Hz) bursts of afferent glutamatergic potentials believed to mediate transmission of the suckling information (27) to oxytocin neurons as well as during the increase in glutamatergic synaptic activity induced by osmotic stimulation (28). If this were the case, the reduced astrocytic coverage of neurons characterizing the SON of lactating and dehydrated animals (13,14) would favor heterosynaptic inhibition of GABA release.…”
Section: Discussionmentioning
confidence: 99%
“…This will prevent the postsynaptic neuron from being contaminated by nonrelevant signals and will serve to increase the signal-to-noise ratio for pertinent information (8). In the SON, glutamate spillover is likely to occur during the brief (2-to 4-s) high-frequency (40-to 80-Hz) bursts of afferent glutamatergic potentials believed to mediate transmission of the suckling information (27) to oxytocin neurons as well as during the increase in glutamatergic synaptic activity induced by osmotic stimulation (28). If this were the case, the reduced astrocytic coverage of neurons characterizing the SON of lactating and dehydrated animals (13,14) would favor heterosynaptic inhibition of GABA release.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Recent work from our laboratory 19 indicated that GABA does not always function as an inhibitory neurotransmitter in this circuit. We demonstrated that, although GABA generally inhibits AVP neurons under resting conditions, it excites them under chronic hyperosmotic stress, a situation that demands increased AVP secretion.…”
mentioning
confidence: 99%
“…In vivo experiments unambiguously showed that glutamate receptor blockers reversibly interrupted phasic activity in VP neurons (Nissen et al, 1994(Nissen et al, , 1995Moos et al, 1997), whereas glutamatergic receptor agonists triggered (Nissen et al, 1995) or accelerated phasic activity. Glutamate was shown to be the sole source of EPSPs in coronal slices in vitro (van den Pol et al, 1990;Wuarin and Dudek, 1993;Yang et al, 1994;Richard and Bourque, 1995;Jourdain et al, 1998). In our cultures, blockade of EPSPs suppressed phasic activity even when firing was triggered and maintained with a depolarizing current indicating that glutamatergic EPSPs are required for generating rhythmic bursts.…”
Section: Role Of Glutamatergic Inputs In Phasic Activitymentioning
confidence: 49%